Trophonella (Gastropoda: Muricidae), a New Genus from Antarctic Waters, with the Description of a New Species - Harasewych, M. G.; Pastorino, Roberto Santiago Guido
The new genus Trophonella is described from the outer shelf and upper continental slope of Antarcticaand islands within the Antarctic Convergence. Four previously known species that had been attributed to the genusTrophon (Trophon scotianus Powell, 1951; T. echinolamellatus Powell, 1951; T. enderbyensis Powell, 1958; and T.eversoni Houart, 1997) are included in Trophonella, as is one new species (Trophonella rugosolamellata) describedherein. Trophonella resembles Trophon in gross shell morphology: the members of both genera have large, globoseshells, paucispiral protoconchs, prominent axial lamellae, and short siphonal canals. Trophonella differs fromTrophon in having shells with evenly rounded whorls that lack a well-defined shoulder; rachidian teeth withdistinctive, broadly triangular central cusps, but that lack the marginal cusps of Trophon; characteristic sphericalaccessory salivary glands; and a circumpapillar fold on the penis that is absent in Trophon. Relationships of thegenera Trophon and Trophonella, as well as of the subfamily Trophoninae are reexamined by supplementing the datamatrix of Kool (1993b, Table 3) with data for additional taxa. Results support the segregation of Trophonella fromTrophon at the generic level. Based on the relationships of the type species of their respective nominotypical genera,Trophoninae is either the sister taxon of a narrowly circumscribed Ocenebrinae, or both are part of a larger clade. Abetter resolved phylogeny containing a much broader sampling of the more than 50 genus-level taxa that have beenattributed to these two subfamilies will be required in order to delineate more precisely the membership of the cladeand to identify its diagnostic synapomorphies. Fil: Harasewych, M. G. National Museum of Natural History; Estados Unidos Fil: Pastorino, Roberto Santiago Guido. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales “Bernardino Rivadavia”; Argentina